The Design of a Social Campaign of Third Culture Kids Using Instagram - Nadhiva, Dalila; Apsari, Diani; Haswati, Sri Maharani Budi (KalaTanda, 2022)
Many of these families begin having children outside of their home country, and the children that grew up there are known as Third Culture Kids (TCK). They define the "third culture" as a lifestyle that involves temporarily relocating to a multicultural area where they live in various communities. This culture is distinct from the culture their parents were raised in and the environment they spend frequently. This subject was intended to aid the students' integration into this nation, particularly in Bandung. Instagram was chosen because they are simple to obtain and most, if not all, students use this platform. The reason is due to the Indonesian TCKs' brief stay in Indonesia, they have a difficult time assimilating into the culture and way of life of the nation as well as only a few platforms are available to aid and unite them with one another. This research will use qualitative and quantitative data, as well as a matrix approach. This research aims to create a social campaign using Instagram posts that will help in introducing Bandung to the Indonesian TCKs together with building a community of people that are alike.